(untitled) (International Journal of Engineering and Computer Science, 2016)
By the rapid development of the computer network during the past few years, the security of information issue comes to be more and more difficult. The Intrusion Detection Systems (IDS) can be used widely for protecting network. Data mining techniques are extensively used, due to some attributes like the scalability, adaptability and validity. This paper focuses on review of the existing intrusion detection system by using data mining techniques and discussing on various disputes in the existing system based on certain classification parameters such as accuracy, detection rate, false alarm etc.